2021
DOI: 10.1007/s11356-021-16986-6
|View full text |Cite
|
Sign up to set email alerts
|

CO2 sequestration by propagation of the fast-growing Azolla spp.

Abstract: Azolla is a group of aquatic floating plants that can achieve very high growth rates compared to other aquatic macrophytes, with a doubling time of 2–5 days under optimal growing conditions. The ability of Azolla to grow at such rapid rates allows for the opportunity of utilizing it as a method to sequester a significant amount of atmospheric CO 2 in the form of biomass, which can be locked away to completely remove the carbon from the active carbon cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
1
9
0
1
Order By: Relevance
“…The percentage of OC content of A. pinnata ranged from 41 to 44% of dry weight. The OC content results of A. pinnata (41 – 44%) obtained from the present study are supported by several other studies, such as - Hamdan and Houri [ 22 ] found average of 42% as well as Bocchi and Malgioglio [ 20 ], Cheng et al [ 40 ] and Speelman et al [ 41 ] reported 39 to 44% OC content of Azolla irrespective of species.
Fig.
…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The percentage of OC content of A. pinnata ranged from 41 to 44% of dry weight. The OC content results of A. pinnata (41 – 44%) obtained from the present study are supported by several other studies, such as - Hamdan and Houri [ 22 ] found average of 42% as well as Bocchi and Malgioglio [ 20 ], Cheng et al [ 40 ] and Speelman et al [ 41 ] reported 39 to 44% OC content of Azolla irrespective of species.
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…The CO 2 sequestration rates of the present study were 154 to 164% and 150 to 157% of the dry weight of A. pinnata in the CD and CU experiments, respectively. According to Hamdan and Houri [ 22 ], 21,266 kg of C/year/ha (equivalent to 21,266 kg × 3.6663 = 77,967 kg CO 2 ) are sequestered by 50,633 kg of Azolla (dry weight), which is equivalent to 154% of the dry weight of Azolla. The CO 2 sequestration rates, as theoretically reported by Hamdan and Houri [ 22 ] strongly support the CO 2 sequestration results of the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogenization in the symbionts evolves hydrogen rather than nitrogen fixation when Azolla anabaena is grown in a nitrogen-free environment and/or a nitrate-rich aquatic medium (Hamdan et al, 2021).…”
Section: Azolla and Bioenergymentioning
confidence: 99%